Satisfaction and perceived impact of virtual learning during COVID‐19 lockdown: A case study of an online nursing research conference - Emmanuel O. Adesuyi; Oluwadamilare Akingbade; Yetunde O. Tola; Oluwadamilola Otun; Damilola M. Faleti; Israel O. Fawole; Daniel D. Faleti; Emmanuel A. Dairo; Olamide Sado; Pelumi Adefehinti; Taiwo Olubunmi Adewa (Wiley, 2023)
Abstract Aim This study aimed to assess nurses' satisfaction and perceptions of the impact of virtual learning. Design A descriptive cross‐sectional survey. Method 236 nurses attending an online conference from several parts of Nigeria participated in the study. Analysed data were summarized and presented in tables and graphs, while linear regression was used to measure the associations. Results Most of the respondents perceived the programme as highly impactful. All three domains: learner‐content interaction (p = 0.020), learner-instructor interaction (p = 0.000) and learner-learner interaction (p = 0.000), were found to be statistically significantly associated with the perceived impact of the programme, and thus statistically significant predictors of the effects of online learning (p = 0.02), (F = 5.471). Conclusively, the Interaction of learners with learning content, lecturers and other learners was seen as determinants of an effective and impactful online education. It is recommended that nursing training institutions embrace online learning either as the leading platform or as an adjunct to a face‐to‐face method.